Characterization of Magnetite and Zinc Oxide Nanoparticles bio-synthesized with Snakeweed (Stachytarpheta Indica) - Ngwu, Comfort (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Biosynthesis or green synthesis was employed for the preparation of magnetite and ZnO nanoparticles using non-hazardous solvents and plant extracts of snake weed. The leaf extract has shown to be rich in polyphenols, which facilitated the reduction and capping of the synthesized metal oxide nanoparticles, as indicated by the FTIR spectra. The nano-ZnO particles appeared spherical and agglomerated in structure with particle sizes of about 2-20 nm, while the bio-magnetite particles had a sheet-like layer that appeared clumped and cracked, with an SEM average grain size of 1-4 nm. The crystallite sizes were 3 and 0.026 nm for both ZnO and Iron nanocomplexes. The various elemental components of the particles in their different proportions were confirmed by the EDX spectra. The crystallinity of the nanoparticles was well defined by the very sharp and broad peaks, although capped by the biomolecules of the snake weed extract. Results indicate that the process can be used as an efficient green and economical alternative to the chemical synthesis of the same and its attendant draw-backs.